Direct action of capsaicin in brown adipogenesis and activation of brown adipocytes. (18th January 2016) - Kida, Ryosuke; Yoshida, Hirofumi; Murakami, Masaru; Shirai, Mitsuyuki; Hashimoto, Osamu; Kawada, Teruo; Matsui, Tohru; Funaba, Masayuki
Abstract : The ingestion of capsaicin, the principle pungent component of red and chili peppers, induces thermogenesis, in part, through the activation of brown adipocytes expressing genes related to mitochondrial biogenesis and uncoupling such as peroxisome proliferator‐activated receptor (Ppar) γ coactivator‐1α (Pgc‐1α) and uncoupling protein 1 (Ucp1). Capsaicin has been suggested to induce the activation of brown adipocytes, which is mediated by the stimulation of sympathetic nerves. However, capsaicin may directly affect the differentiation of brown preadipocytes, brown adipocyte function, or both, through its significant absorption. We herein demonstrated that Trpv1, a capsaicin receptor, is expressed in brown adipose tissue, and that its expression level is increased during the differentiation of HB2 brown preadipocytes. Furthermore, capsaicin induced calcium influx in brown preadipocytes. A treatment with capsaicin in the early stage of brown adipogenesis did not affect lipid accumulation or the expression levels of Fabp4 (a gene expressed in mature adipocytes), Pparγ2 (a master regulator of adipogenesis) or brown adipocyte‐selective genes. In contrast, a treatment with capsaicin in the late stage of brown adipogenesis slightly increased the expression levels of Fabp4, Pparγ2 and Pgc‐1α . Although capsaicin did not affect the basal expression level of Ucp1, Ucp1 induction by forskolin was partially inhibited by capsaicin, irrespective of the dose of capsaicin. The results of the present study suggest the direct effects of capsaicin on brown adipocytes or in the late stage of brown adipogenesis.